Perkembangan Teori Sewa Tanah dalam Perspektif Pemikiran Ekonomi - Sumargo, Bagus (Journal the Winners: Economics, Business, Management, and Information System Journal, 2002)
A history of Land Rent Theorities have several opinions, as mazhab of Physiocratic, classical tradition, and new.Â  The different opponions can be understanding for knowing two factors that land value increasingly location to central bussines and fertile soil.